Istinsyaq Sebagai Terapi Alternatif Pada Penderita Rinosinusitis Kronik Tahun 2022 - Kesya Azzahra Putri; Mochammad Erwin Rachman; Sri Wahyu; Rachmat Faisal Syamsu; Mohammad Reza Zainal Abidin (NERSMID : Jurnal Keperawatan dan Kebidanan, 2024)
The aim of this research is to determine the effect of istinsyaq as an alternative therapy on sufferers of chronic rhinosinusitis at Ibnu Sina Hospital in 2022. The method of this research is Pre-Post Experimental research using a one group pre-post test approach without control, by making the first observation ( pre-test) which makes it possible to test changes that occur after the experiment by conducting a second observation (post-test). The data source used in this research is primary data taken from the Sino Nasal Outcome-22 questionnaire which was taken before and after the patient performed istinsyaq. Results: The level of chronic rhinosinusitis symptom scale that is felt by many samples suffering from chronic rhinosinusitis whether they have had surgery or not is included in the severe type scale and moderate type scale categories. Istinsyaq is effectively used as an alternative therapy for chronic rhinosinusitis sufferers in that the scale of symptoms decreases after the intervention is given, there is a decrease in the number of scales.